The Relationship Between Select Demographic Characteristics and Body Mass Index Among Native Hawaiian and Other Pacific Islander Caregiving Adults. (January 2015) - Duncan, Katrina L.; Lassetter, Jane H.; VanServellen, Gwen; Brown, Lora Beth; Clark, Lauren; Morgan, Sharla; Curtis, Samantha; Alleger, Brooke; Coleman, Jaclyn; Muffler, Arielle; Miyamoto, Shemnon; Mounga, Va; et al.
Purpose: Native Hawaiian and other Pacific Islanders (NHOPIs) have the highest prevalence of overweight and obesity in the world. We identified the proportion of our NHOPI sample in each body mass index (BMI) category and explored relationships between BMI and demographic characteristics.Design/Method: Our descriptive correlational study included 364 NHOPI caregiver adults in Utah ( n = 155) and Hawaii ( n = 209). We gathered demographic information with a questionnaire. Height and weight were measured for BMI calculations.Results: According to the Centers for Disease Control and Prevention's BMI categories, 84.3% of our sample was overweight or obese. Participants in Utah had significantly higher BMIs than participants in Hawaii. Educational attainment was inversely related with BMI; however, age, gender, and income were not significantly related with BMI.Discussion: NHOPIs on the U.S. mainland may be at greater risk for obesity than those in Hawaii; food price differences between locations may help explain this. NHOPIs in early adulthood had high BMIs; overtime this situation could worsen without intervention.Implications for practice: NHOPIs with low education levels or in areas of low food prices are at increased risk for obesity. Future research should focus on culturally sensitive interventions to reduce NHOPI obesity and associated risks.